Understanding Corruptors’ Imagination Concerning Money Through Their Metaphors - Dhuha Hadiyansyah; Didin Nuruddin Hidayat (IJEE (Indonesian Journal of English Education), 2019)
ABSTRACTThis study illustrates the imagination of corrupt politicians from the Prosperous Justice Party (PKS) about money through observing the metaphors they use to replace the word "money" when conducting cell phone conversations revealed in court. The discussion focuses on the metaphorical expressions of two PKS politicians, in the case of bribery by Commissioner of PT Cahaya Mas Perkasa, So Kok Seng, related to road reconstruction projects in Maluku and North Maluku in 2017. The Conceptual Metaphor theory is used to uncover the semantic fields of the metaphors they create. Thus, the corruptor's imagination can be revealed. It was found that through metaphors they think of money as a sacred object like the Holy Book.ABSTRAKStudi ini menganalisa imajinasi politisi korup dari Partai Keadilan Sejahtera (PKS) tentang uang dengan mengamati metafora yang mereka gunakan untuk mengganti kata "uang" ketika melakukan percakapan telepon seluler yang diungkapkan di pengadilan. Penelitian ini berfokus pada ekspresi metaforis dari dua politisi PKS, dalam kasus suap oleh Komisaris PT Cahaya Mas Perkasa, So Kok Seng, terkait dengan proyek rekonstruksi jalan di Maluku dan Maluku Utara pada tahun 2017. Teori Metafor Konseptual digunakan untuk mengungkap bidang semantik dari metafora yang mereka buat. Dengan demikian, imajinasi koruptor dapat terungkap. Melalui metafora mereka menganggap uang sebagai objek suci seperti Kitab Suci. How to Cite: Hadiyansyah, D., Hidayat, D.N. (2019). Understanding Corruptors’ Imagination Concerning Money Through Their Metaphors. IJEE (Indonesian Journal of English Education), 6(2), 109-118. doi:10.15408/ijee.v6i2.15465.